(X+2)(x+3)=40

Simple and best practice solution for (X+2)(x+3)=40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X+2)(x+3)=40 equation:



(X+2)(X+3)=40
We move all terms to the left:
(X+2)(X+3)-(40)=0
We multiply parentheses ..
(+X^2+3X+2X+6)-40=0
We get rid of parentheses
X^2+3X+2X+6-40=0
We add all the numbers together, and all the variables
X^2+5X-34=0
a = 1; b = 5; c = -34;
Δ = b2-4ac
Δ = 52-4·1·(-34)
Δ = 161
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(5)-\sqrt{161}}{2*1}=\frac{-5-\sqrt{161}}{2} $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(5)+\sqrt{161}}{2*1}=\frac{-5+\sqrt{161}}{2} $

See similar equations:

| x/7=200 | | (z-50)+(z-50)=z | | 47-3+7m=18+8m-m | | 2+x=103 | | x2-4x+12=6x-2 | | t-33=67 | | -15/2=3x | | 8x^2-9x-221=0 | | 2y-44=-8(y-2) | | 124+y+15=154 | | x3=3x | | 9x-101=34 | | 2(x-17=14 | | 5(w-2)+8w=16 | | 5/43x+20/43=20/43 | | -23=w/5-3 | | 17m-30=60-m | | 2x-12x-9=11 | | 15+b=54 | | x²+12x+20=0 | | 3x-2(-1)=6 | | 0.1666666667(y+42)-15=-3 | | 0=12000+.6x | | (3x+10)+x=180 | | 15+5n=18+2n | | 9x-101=146 | | 9x-4=10*1 | | C^-10c+21=0 | | 5(3x-7)(5x+4)=0 | | 121=11g | | 53+8n=13+2n | | 62+7x+28=17x |

Equations solver categories